THE INFLUENCE OF NUTRITIONAL STATUS ON COGNITIVE DEVELOPMENT PRE-SCHOOL AGE CHILDREN - Dewi Pangestuti; Surya Akbar; Mayang Sari Ayu (RADJA PUBLIKA, 2023)
Early childhood period is in dire need of good nutrition. Poor nutritional statuscan cause delays in children's cognitive development. Nutrition report global (2020), statedthe whole countryexperiencing nutritional problems. Globally, the most children with malnutrition problems are in Sub-Saharan Africa.Indonesia is experiencing a triple burden of disease, namely malnutrition, obesity and stunting. The aim of the study was to analyze the effect of nutritional status on the cognitive development of pre-school aged children. This research approachis a retrospective cohort analytic study with a sampling technique using purposive sampling. This study was conducted using data from 79 children aged 5-6 years from early childhood education school students. Nutritional status is determined using anthropometry by measuring body weight and height based on the child's age. Assessing children's cognitive abilities using instruments from the Mini Mental State Examination (MMSE) questionnaire. The results showed that 72.2% of children's nutritional status was normal and 72.2% of children's cognitive development was normal. Data analysis was based on the chi-square test, p-value = 0.011 (p <0.05), with a relative risk value of 2.591. Shows that nutritional status has an effect of 2.591 times on the cognitive development of pre-school age children.